2019
DOI: 10.1021/acsami.9b14876
|View full text |Cite
|
Sign up to set email alerts
|

High-Efficiency Bifacial Dye-Sensitized Solar Cells for Application under Indoor Light Conditions

Abstract: High-efficiency, stable bifacial dye-sensitized solar cells (DSSCs) are prepared for application under indoor light conditions. A 3-methoxypropionitrile solvent and cobalt redox couples are utilized to prepare the electrolytes. To obtain the best cell performance, the components of the DSSCs, including electrolytes, photoanodes, and counter electrodes (CEs), are regulated. The experimental results indicate that an electrolyte comprising a Co (II/III) ratio of 0.11/0.025 M, 1.2 M 4-tert-butylpyridine, Y123 dye,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 39 publications
0
57
0
Order By: Relevance
“…[ 2–4 ] DSCs are currently the most efficient solar cell technology in low light conditions, which makes them excellent candidates for building and automobile integrated photovoltaics and to power sensors, appliances for the Internet of Things (IoT), and portable devices. [ 5–10 ] Recent developments of new photoanodes, counter electrodes, dyes, and co‐adsorption strategies have further improved device efficiencies. [ 11–28 ] Furthermore, the improved stabilities and efficiencies of aqueous DSCs open up new opportunities for the sustainability of these devices.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2–4 ] DSCs are currently the most efficient solar cell technology in low light conditions, which makes them excellent candidates for building and automobile integrated photovoltaics and to power sensors, appliances for the Internet of Things (IoT), and portable devices. [ 5–10 ] Recent developments of new photoanodes, counter electrodes, dyes, and co‐adsorption strategies have further improved device efficiencies. [ 11–28 ] Furthermore, the improved stabilities and efficiencies of aqueous DSCs open up new opportunities for the sustainability of these devices.…”
Section: Introductionmentioning
confidence: 99%
“…Venkatesan et al optimized the thickness of their platinum counter electrodes to allow for backside illumination. 41 Huang et al proposed a titanium foil as anode current collector instead of the traditional glass:conductive oxide design. 42 Kapil et al designed their entire DSC around a cylindrical titanium foil to allow for omnidirectional photon harvesting.…”
Section: Dye-sensitized Solar Cells: Materials and Devicesmentioning
confidence: 99%
“… 61,62 One year later, Venkatesan et al achieved an open-circuit voltage of 850 mV and a conversion efficiency of 24.5% at 1000 lx. 41 In 2017, Freitag et al reported on the indoor performance of DSCs based on a copper complex-based redox electrolyte. Devices based on the Cu II/I (tmby) 2 (tmby = 4,4′,6,6′-tetramethyl-2,2′-bipyridine) redox couple (870 mV vs. NHE) achieved 28.9% power conversion efficiency at 1000 lx.…”
Section: Dye-sensitized Solar Cells: Materials and Devicesmentioning
confidence: 99%
“…This phenomenon can improve the PCE of a DSSC in an indoor environment. Venkatesan and co-workers fabricated a highly efficient (PCE values of 22.66%, 23.48%, and 24.52% under illuminations of 201.8 lx, 607.8 lx, and 999.6 lx, respectively) bi-facial DSSC for indoor applications [ 94 ], using the Y123 dye as a sensitizer. Grätzel and co-workers fabricated a DSSC using XY1b/Y123 as a sensitizer, which exhibited a high PCE (32%) under the illumination of a 1000 lx Osram 930 warm white fluorescent lamp [ 78 ].…”
Section: Pv Cells For Indoor Applicationsmentioning
confidence: 99%